2016
DOI: 10.5424/fs/2016253-09787
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of height-diameter models based on geographically weighted regressions and linear mixed modelling applied to large scale forest inventory data

Abstract: Aim of the study: The main objective of this study was to test Geographically Weighted Regression (GWR) for developing heightdiameter curves for forests on a large scale and to compare it with Linear Mixed Models (LMM).Area of study: Monospecific stands of Pinus halepensis Mill. located in the region of Murcia (Southeast Spain). Materials and Methods:The dataset consisted of 230 sample plots (2582 trees) from the Third Spanish National Forest Inventory (SNFI) randomly split into training data (152 plots) and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…However, there are many differences between the LMM and GWR model. For example, Quirós-Segovia et al (2016) discovered that the quality of the height-diameter models of GWR and LMM regressions were comparable. Wei et al (2019) studied the spatial distribution of PM2.5 and found that the LMM was better than the GWR model; however, the GWR model has been shown to perform better than the LMM in many other studies (Liu et al 2014, Zhang & Gove 2005.…”
Section: Model Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are many differences between the LMM and GWR model. For example, Quirós-Segovia et al (2016) discovered that the quality of the height-diameter models of GWR and LMM regressions were comparable. Wei et al (2019) studied the spatial distribution of PM2.5 and found that the LMM was better than the GWR model; however, the GWR model has been shown to perform better than the LMM in many other studies (Liu et al 2014, Zhang & Gove 2005.…”
Section: Model Comparisonmentioning
confidence: 99%
“…However, spatial effects in data often appear in the form of patches or geographic gradients, which can violate the independence and homogeneity assumptions of OLS and other traditional statistical methods (Green et al 2005, Subedi et al 2018. To this end, to include spatial effects in the regression framework, scholars have used spatial regression models, which estimate the covariance matrix to model the spatial autocorrelation of variables in adjacent locations; examples include the spatial lag model (SLM), the spatial error model (SEM) and the linear mixed model (LMM - Anselin 2001, Lu & Zhang 2011, Quirós-Segovia et al 2016, Qi et al 2020). The GWR model fits the spatial relationship of each location within a given bandwidth, explores the nonstationarity of a space and enhances the description and prediction of the spatial distribution, which makes it a very attractive tool for forestry modeling (Brunsdon et al 1996, Mennis 2006.…”
Section: Introductionmentioning
confidence: 99%